Coherence and Cohesion: An Analysis of Descriptive Paragraphs Written by Eleventh Grade Students of SMA Negeri 2 Gerokgak - Dewi, Komang Putri; Ramendra, Dewa Putu; Adnyani, Ni Luh Putu Sri (EDULIA: English Education, Linguistic and Art Journal, 2025)
This study aims to examine aspects of cohesion and coherence in descriptive paragraphs written by grade XI students of SMA Negeri 2 Gerokgak. Both aspects play an important role in conveying information in a clear and structured manner. This research uses a mixed method approach with an explanatory sequential design that combines quantitative and qualitative methods. Sampling was done through cluster random sampling method with a lottery system, and class XI-3 was selected as the research sample. The results showed that the majority of students were quite capable of writing descriptive paragraphs that were quite coherent and used cohesion devices appropriately. However, there were still students who had difficulty in maintaining consistency and logical flow in their writing. This finding emphasizes the importance of the teacher's role in instilling an understanding of cohesion and coherence in the writing learning process. With proper application of these two concepts, students can produce more systematic and communicative writing. Therefore, writing lessons that emphasize cohesion and coherence need to be continuously developed to improve the overall quality of students' writing.   Keywords: Coherence, Cohesion, and Descriptive Paragraph